Debiasing policymakers: The role of behavioral economics training - Ana María Rojas; Carlos G. Scartascini (Inter-American Development Bank (IDB), 2024)
Behavioral biases often lead to suboptimal decisions, a vulnerability that extends to policymakers who operate under conditions of fatigue, stress, and time constraints and with significant implications for public welfare. While behavioral economics offers strategies like default adjustments to mitigate decision-making costs, deploying these policy interventions is not always feasible. Thus, enhancing the quality of policy decision-making is crucial, and evidence suggests that targeted training can boost job performance among policymakers. This study evaluates the impact of a behavioral training course on policy decision-making through a randomized experiment and a survey test that incorporates problem-solving and decision-making tasks among approximately 25,000 participants enrolled in the course. Our findings reveal a significant improvement in the treated group, with responses averaging 0.6 standard deviations better than those in the control group. Given the increasing prevalence of such courses, this paper underscores the potential of behavioral training in improving policy decisions and advocates for further research through additional experimental studies.
Keywords: H83; Z18; 330; Experimental design; Behavioral economics; Training; Public policy; Government officials